2019
DOI: 10.3390/ma12040614
|View full text |Cite
|
Sign up to set email alerts
|

The Supramolecular Organogel Formed by Self-Assembly of Ursolic Acid Appended with Aromatic Rings

Abstract: Ursolic acid (UA) as a natural ursane-triterpenoid has rich pharmacological activities. We have found that it possesses aggregation properties and could self-assemble into organogels. Based on the aggregation property of ursolic acid in suitable solvents, its derivative appended with aromatic rings by amide groups was synthesized. The property of self-assembly into organogel was studied in this paper. The results revealed that this derivative could form supramolecular gel in halogenated benzene and also gelate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
(36 reference statements)
0
13
0
Order By: Relevance
“…Some triterpenes, including oleanolic acid, are known as materials forming gels in organic solutions. Such organogels can be useful as matrixes in the synthesis of gold nanoparticles or as potential drug carriers, and interest in other possible applications of these systems is still growing. , Here, we demonstrated that the rheological properties of oleanolic acid can be modulated by human serum albumin, and this finding may be useful for designing drug formulations based on oleanolic acid as the API. Interfacial shear rheology is also linked to the long-term stability of thin films at interfaces, thus the results of our study can be helpful in predicting the stability and shelf life of pharmaceutical dispersions containing oleanolic acid and albumin.…”
Section: Resultsmentioning
confidence: 79%
“…Some triterpenes, including oleanolic acid, are known as materials forming gels in organic solutions. Such organogels can be useful as matrixes in the synthesis of gold nanoparticles or as potential drug carriers, and interest in other possible applications of these systems is still growing. , Here, we demonstrated that the rheological properties of oleanolic acid can be modulated by human serum albumin, and this finding may be useful for designing drug formulations based on oleanolic acid as the API. Interfacial shear rheology is also linked to the long-term stability of thin films at interfaces, thus the results of our study can be helpful in predicting the stability and shelf life of pharmaceutical dispersions containing oleanolic acid and albumin.…”
Section: Resultsmentioning
confidence: 79%
“…Furthermore, UA is a natural molecule with self-assembly properties, which can combine with other chemical molecules to form supramolecular compounds with specific structures and properties ( Lu et al, 2019 ; Grosu et al, 2020 ). Paclitaxel (PTX) is one of the chemotherapeutic drugs widely used in clinic.…”
Section: Review Of Ua Nanoformulationsmentioning
confidence: 99%
“…Furthermore, the author introduced the aromatic ring into the molecular structure of ursolic acid through the connection of the amide bond. Using the π-π stacking effect of the aromatic ring and the hydrogen bonding effect of the amide bond, ursolic acid can also self-assemble into a transparent nanofiber organogel in other aromatic solvents, such as chlorobenzene, which provided a new idea for the design of supramolecular gels [86].…”
Section: Other Natural-drugs-based Low-molecular-weight Supramolecular Gelsmentioning
confidence: 99%